Human life safety as the method for forming professional competencies for sustainable development - Dashkevich, Tatsiana V.; Bogacheva, Ekaterina S. (Journal of the Belarusian State University. Ecology, 2021)
The article discusses the relevance of studying safety problems and the formation of a safety culture for specialists. In the modern world, with the development of technologies, the need for specialists who have knowledge in the field of sustainable development, are able to ensure the safe implementation of any type of activity, assess the risks and scale of consequences, including analyzing the previous experience of mistakes and wrong decisions, increases. Special attention is paid to educational technologies for the formation of the competencies of safe life in students of higher education institutions in modern conditions.
Keywords: life safety; safety culture; educational technologies; case-method; competencies